From reverse transcription to human brain tumors - Dmitrenko, V.V.; Avdieiev, S.S.; Areshkov, P.O.; Balynska, O.V.; Bukreieva, T.V.; Stepanenko, A.A.; Chausovskii, T.I.; Kavsan, V.M. (Вiopolymers and Cell, 2013)
Reverse transcriptase from avian myeloblastosis virus (AMV) was the subject of the study, from which the investigations of the Department of biosynthesis of nucleic acids were started. Production of AMV in grams quantities and isolation of AMV reverse transcriptase were established in the laboratory during the seventies of the past century and this initiated research on the cDNA synthesis, cloning and investigation of the structure and functions of the eukaryotic genes. Structures of salmon insulin and insulin-like growth factor (IGF) family genes and their transcripts were determined during long-term investigations. Results of two modern techniques, microarray-based hybridization and SAGE, were used for the identification of the genes differentially expressed in astrocytic gliomas and human normal brain. Comparison of SAGE results on the genes overexpressed in glioblastoma with the results of microarray analysis revealed a limited number of common genes. 105 differentially expressed genes, common to both methods, can be included in the list of candidates for the molecular typing of glioblastoma. The first experiments on the classification of glioblastomas based on the data of the 20 genes expression were conducted by using of artificial neural network analysis. The results of these experiments showed that the expression profiles of these genes in 224 glioblastoma samples and 74 normal brain samples could be according to the Kohonen’s maps. The CHI3L1 and CHI3L2 genes of chitinase-like cartilage protein were revealed among the most overexpressed genes in glioblastoma, which could have prognostic and diagnostic potential. Results of in vitro experiments demonstrated that both proteins, CHI3L1 and CHI3L2, may initiate the phosphorylation of ERK1/ ERK2 and AKT kinases leading to the activation of MAPK/ERK1/2 and PI3K/AKT signaling cascades in human embryonic kidney 293 cells, human glioblastoma U87MG, and U373 cells. The new human cell line 293_CHI3L1, stably producing chitinase-like protein CHI3L1 was developed and these cells were found to have an accelerated growth rate and could undergo anchorage-independent growth in soft agar which is one of the most consistent indicators of oncogenic transformation. The formation of tumors in rats by 293_CHI3L1 cells evidences that CHI3L1 is an oncogene involved in tumorigenesis. In vitro experiments showed that constitutive expression of CHI3L1 gene promotes chromosome instability in 293 cells. Наукові розробки відділу біосинтезу нуклеїнових кислот розпочато з вивчення зворотної транскриптази вірусу пташиного мієлобластозу (AMV). Протягом сімдесятих років минулого століття у відділі налагоджено виробництво AMV (декілька грамів на рік) та виділення зворотної транскриптази AMV, що дозволило розгорнути роботи з синтезу кДНК, клонування та вивчення структури і функції генів евкаріотів. Упродовж багаторічних досліджень було визначено будову генів інсуліну і родини інсуліноподібних факторів росту (IGF) лосося та їхніх транскриптів. Результати застосування двох сучасних методів – гібридизації мікрочіпів і SAGE – використано для ідентифікації генів, які диференційно експресуються в астроцитарних гліомах і нормальному головному мозку людини. Їхнє порівняння виявило обмежену кількість спільних генів, надекспресованих у гліобластомі. Визначені нами 105 диференційно експресованих генів, спільних для обох методів, можуть бути включені до переліку кандидатів для молекулярного типування гліобластом. Проведено перші експерименти з класифікації гліобластом на основі даних по експресії 20 генів із застосуванням штучної нейронної мережі, які показали, що профілі експресії зазначених генів для 224 зразків гліобластом і 74 зразків нормального головного мозку піддаються кластеризації згідно з картами Кохонена. Серед найекспресованіших у гліобластомі генів, які мають прогностичний і діагностичний потенціал, виявлено гени хітиназоподібних білків CHI3L1 і CHI3L2. Результати експериментів in vitro продемонстрували, що обидва білки – CHI3L1 і CHI3L2 – здатні ініціювати фосфорилювання кіназ ERK1/ERK2 і AKT, що спричиняє активацію сигнальних каскадів PI3K/AKT і MAPK/ERK1/2 в клітинах 293 ембріональної нирки людини, а також у клітинах U87MG і U373 гліобластоми людини. Ідентифіковано нову клітинну лінію людини 293_CHI3L1, яка стабільно продукує хітиназоподібний білок CHI3L1. Знайдено, що ці клітини мають прискорений ріст і можуть рости у м’якому агарі незалежно від прикріплення до поверхні, що є одним із найсуттєвіших показників пухлинної трансформації. Формування пухлин клітинами 293_CHI3L1 у щурів свідчить про те, що CHI3L1 є онкогеном, причетним до канцерогенезу. Експерименти in vitro засвідчили, що конститутивна експресія гена CHI3L1 сприяє хромосомній нестабільності у клітинах 293. Модальне число хромосом у клітинах 293_CHI3L1 відрізняється від такого хромосом у контрольних клітинах 293_pcDNA3.1, трансфікованих «порожнім» плазмідним вектором, і батьківських клітинах 293. Научные разработки отдела биосинтеза нуклеиновых кислот начались с изучения обратной транскриптазы вируса птичьего миелобластоза (AMV). В течение семидесятых годов прошлого века в отделе налажено производство AMV (несколько граммов в год) и выделение обратной транскриптазы AMV, что позволило развернуть работы по синтезу кДНК, клонированию и исследование структуры и функции генов эукариотов. На протяжении многолетних исследований было определено строение генов инсулина и семейства инсулиноподобных факторов роста (IGF) лосося и их транскриптов. Результаты применения двух современных методов – гибридизации микрочипов и SAGE – использованы для идентификации генов, дифференциально экспрессируются в астроцитарных глиомах и нормальном головном мозге человека. Их сравнение выявило ограниченное число общих генов, надэкспрессиро- ванных в глиобластоме. Определенные нами 105 дифференциально экспрессированных генов, общих для обоих методов, могут быть включены в список кандидатов для молекулярного типирования глиобластом. Проведены первые эксперименты по классификации глиобластом на основе данных по экспрессии 20 генов с использованием искусственной нейронной сети, показавшие, что профили экспрессии этих генов для 224 образцов глиобластом и 74 образцов нормального головного мозга могут быть кластеризованы в соответствии с картами Кохонена. Среди наиболее надэкспресированных в глиобластоме генов, имеющих прогностический и диагностический потенциал, обнаружены гены хитиназоподобных белков CHI3L1 и CHI3L2. Результаты экспериментов in vitro продемонстрировали, что оба белка – CHI3L1 и CHI3L2 – могут инициировать фосфорилирование киназ ERK1/ ERK2 и AKT, приводящее к активации сигнальных каскадов PI3K/ AKT и MAPK/ERK1/2 в клетках 293 эмбриональной почки человека, а также в клетках U87MG и U373 глиобластомы человека. Получена новая клеточная линия человека 293_CHI3L1 со стабильной продукцией хитиназоподибного белка CHI3L1. Обнаружено также, что эти клетки обладают ускоренным ростом и могут расти в мягком агаре независимо от прикрепления к поверхности. Такие свойства являются одним из наиболее существенных показателей опухолевой трансформации. Формирование опухолей клетками 293_CHI3L1 у крыс свидетельствует о том, что CHI3L1 является онкогеном, участвующим в канцерогенезе. Эксперименты in vitro показали, что конститутивная экспрессия гена CHI3L1 способствует хромосомной нестабильности в клетках 293. Модальное число хромосом в клетках 293_CHI3L1 отличается от такового хромосом в контрольных клетках 293_ pcDNA3.1, трансфецированных «пустым» плазмидным вектором, и родительских клетках 293.